Enlargement of female pupils when perceiving something cute - Kana Kuraguchi (Nature Portfolio, 2021)
Abstract It is reported that women’s pupils dilate when they see a baby; it is unclear if this pupillary response is caused by the perception of cuteness itself. Since many objects besides babies can be perceived as cute, we investigated whether the perception of cuteness, or the type of object observed, is related to pupil dilation. In the first experiment, female participants were requested to rate the subjective cuteness of greyscale pictures of objects such as animals and foods; their pupil sizes were measured. The results showed a significant positive correlation between perceived cuteness and participants’ pupil dilation. In the second experiment, participants rated the cuteness of images of female faces. Results revealed a significant negative correlation between perceived cuteness and pupil dilation. In our study, perceiving cuteness enlarged female observers’ pupils except when observing female faces. Positive reactions associated with cuteness may be premised on the existence of unconscious perceptual alterations and physical responses.